Peterson's guide to graduate programs in business, education, health, and law, 1996. - Peterson's Guides, Inc. (Princeton, N.J. Peterson's Guides, 1996)
Annual
Continued by: Peterson's graduate programs in business, education, health, information studies, law & social work.
Keywords: Universities and colleges -- Graduate work -- United States -- Directories; Business education -- United States -- Directories; Education -- Graduate work -- United States -- Directories; Education, Graduate -- Canada -- Directories; Education, Graduate -- United States -- Directories; Health occupations schools -- United States -- Directories; Law -- Study and teaching (Graduate) -- United States -- Directories; Schools, Health Occupations -- Canada -- Directories; Schools, Health Occupations -- United States -- Directories; Universities and colleges -- Graduate work -- Canada -- Directories; Universities -- Canada -- Directories; Universities -- United States -- Directories